L’ESPACE COMME RÉINVENTION DU SOI CHEZ HÉLÈNE FRÉDÉRICK ET JOCELYNE SAUCIER - BEAULÉ, Sophie (Studia Universitatis Babeș-Bolyai Philologia, 2018)
Space as Reinvention of the Self in Hélène Frédérick and Jocelyne Saucier. In both Forêt contraire (2014), by Hélène Frédérick, and Il pleuvait des oiseaux (2011), by Jocelyne Saucier, a forest becomes a place of personal transformation, through which characters undergo a ritual of passage. In the separation phase, as anthropologist Victor Turner calls it, the characters leave the community to enter the forest, a liminary space in which they can resolve their problems of identity. Within the sacred space of the forest, cabins play a key role, as they allow not only interpersonal communication but also the expression of art. Art is the means by which the characters are reintegrated into the society to which they return. REZUMAT. Spațiu ca reinvenție a sinelui la Hélène Frédérick și Jocelyne Saucier. În Forêt contraire (2014) de Hélène Frédérick și Il pleuvait des oiseaux (2011) de Jocelyne Saucier pădurea devine un loc al transformării personale unde fiecare personaj est supus unui ritual de trecere. În faza separării, cum o numește antropologul Victor Tuner, personajele părăsesc comunitatea pentru a intra în pădure, un spațiu liminar în care pot să își rezolve problemele de identitate. În spațiul sacru al pădurii, cabanele joacă un rol cheie, fiindcă permit nu numai comunicarea interpersonală, ci și exprimarea artistică. Arta este scopul prin care fiecare personaj e reintegrat în societatea în care se va reîntoarce. Cuvinte cheie: pădure, ritual de trecere, foc, cabană, Jocelyne Saucier, Hélène Frédérick.